Determinants of Financial Inclusion Information Disclosure of Islamic Rural Banks in Indonesia - Fuis Sukma Ayu; Dian Filianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Tujuan dari penelitian ini untuk mengetahui pengaruh dari adanya ukuran bank, umur bank, aktivitas sosial, dan probabilitas terhadap pengungkapan informasi inklusi keuangan di sektor perbankan pada bank pembiayaan rakyat syariah di Indonesia baik secara parsial maupun simultan. Model yang digunakan dalam penelitian ini adalah analisis regresi data panel dengan metode kuantitaif, Aplikasi statistik yang digunakan program Eviews 12. Hasil Penelitian ini menggambarkan dalam parsial bahwa umur BPRS dan CRS memiliki pengaruh positif signifikan terhadap pengungkapan informasi inklusi keuangan, sedangkan dalan ukuran BPRS memiliki pengaruh negative signifikan, kemudian ROA berpengaruh negatif tidak signifikan terhadap pengungkapan informasi inklusi keuangan pada bank pembiayaan rakyat syariah di Indonesia. Namun, secara simultan ukuran BPRS, CRS, umur BPRS dan ROA memiliki pengaruh positif signifikan terhadap pengungkapan informasi inklusi keuangan pada bank pembiayaan rakyat syariah di Indonesia dalam periode 2016-2020. Adapun keterbatasan objek dalam penelitain hanya 32 dari 163 BPRS yang terdaftar di OJK. Penelitian ini diharapkan dapat menjadi evaluasi ataupun masukkan bagi regulator dan BPRS, jika pengungkapan informasi inklusi keuangan sebaiknya diterapkan secara transparan oleh seluruh BPRS, maka dapat meningkatkan reputasi dan kepercayaan dalan menggunakan layanan BPRS. Kata Kunci: ukuran bank, aktivitas sosial, umur bank, profitabilitas, pengungkapan informasi inklusi keuangan.   ABSTRACT The purpose of this study was to determine the effect of the existence of bank size, bank age, social activity, and probability on the disclosure of financial inclusion information in the banking sector at Islamic Rural banks in Indonesia either partially or simultaneously. The model used in this study was panel data regression analysis with quantitative methods, statistical applications used by the author was the Eviews 12 program. The results of this study illustrate in partial terms that the age of IRB and CRS has a significant positive effect on disclosure of financial inclusion information, while the size of the IRB has a significant positive effect on the disclosure of financial inclusion information. significant negative, then ROA has no significant negative effect on the disclosure of financial inclusion information in Islamic Rural Banks in Indonesia. However, simultaneously the size of the IRB, CRS, the age of the IRB and ROA have a significant positive effect on the disclosure of financial inclusion information in Islamic Rural bank in Indonesia in the 2016-2020 period. As for the limitations of the object in the research, only 32 out of 163 IRB are registered with the Financial Service Authority. This research is expected to be an evaluation or input for regulators and IRB, if disclosure of financial inclusion information should be implemented transparently by all IRB, it can increase reputation and trust in using IRB services. Keywords: bank size, social activity, bank age, profitability, disclosure of financial inclusion information.   REFERENCES Afrin, S., Haider, M.Z. & Islam, M.S. (2017). Impact of financial inclusion on technical efficiency of paddy farmers in Bangladesh. Agricultural Finance Review, 77(4), 484-505. https://doi.org/10.1108/AFR-06-2016-0058 Ali, M.M., Devi, A., Furqani, H. & Hamzah, H. (2020). Islamic financial inclusion determinants in Indonesia: an ANP approach. International Journal of Islamic and Middle Eastern Finance and Management, 13(4), 727-747. https://doi.org/10.1108/IMEFM-01-2019-0007 Alm El-Din, M.M., El-Awam, A.M., Ibrahim, F.M. & Hassanein, A. (2022). Voluntary disclosure and complexity of reporting in Egypt: The roles of profitability and earnings management. Journal of Applied Accounting Research, 23(2), 480-508. https://doi.org/10.1108/JAAR-09-2020-0186. Amari, M. & Anis, J. (2021). Exploring the impact of socio-demographic characteristics on financial inclusion: empirical evidence from Tunisia. International Journal of Social Economics, 48(9), 1331-1346. https://doi.org/10.1108/IJSE-08-2020-0527. Ascarya., Rahmawati, S., & Tanjung, H. (2016). Design and determine holistic financial inclusion index for baitul maal wat tamwil design and determine holistic financial inclusion index for baitul maal wat tamwil. Conference: 2nd International Conference on IPAFEM. Yogyakarta Babajide, A. A., Adegboye, F. B., & Omankhanlen, A. E. (2015). Financial Inclusion and Economic Growth in Nigeria. International Journal of Economics and Financial Issues, 5(3), 629–637. Bose, S., Saha, A., Khan, H. Z., & Islam, S. (2017). Non-financial disclosure and market-based firm performance: The initiation of financial inclusion. Journal of Contemporary Accounting & Economics, 13(3), 263–281. https://doi.org/10.1016/j.jcae.2017.09.006 Das, S. (2021). Pengungkapan informasi inklusi keuangan: Bukti empiris dari industri perbankan Bangladesh. Jurnal Global Bisnis, Ekonomi dan Manajemen, 11(1), 27-41. Fitriana, N. L., & Prastiwi, A. (2014). Faktor-faktor yang mempengaruhi luas pengungkapan sukarela dalam annual report. Diponegoro Journal of Accounting, 642-651. Griselda, I. A., Murhadi, WR., & Utami, M. (2020). Pengaruh tanggung jawab sosial perusahaan terhadap kinerja perusahaan sektor pertambangan yang tercatat di Bursa Efek Indonesia & Malaysia 2014-2018. Jurnal Kewirausahaan & Bisnis, 1(1), 21-30. Haldar, P. K., Rahman, S. M. M., Mia, S., Ahmed, F., & Bashawir, A. (2016). Assessing the role of corporate social responsibility practices of commercial banks in enhancing financial inclusion: A study on banking sector in Bangladesh. International Journal of Economics and Financial Issues, 6(4), 1778–1783. Hossain, M., & Hammami, H. (2009). Advances in accounting, incorporating advances in international accounting voluntary disclosure in the annual reports of an emerging country: The case of Qatar. International Journal of Cardiology, 25(2), 255–265. https://doi.org/10.1016/j.adiac.2009.08.002 Jaya, I. G. N. M., & Sunengsih, N. (2009). Kajian analisis regresi dengan data panel. Prosiding Seminar Nasional Penelitian. Universitas Negeri Yogyakarta. Nur, M., & Priantinah, D. (2012). Analisis faktor-faktor yang mempengaruhi pengungkapan corporate social responsibility di Indonesia (Studi empiris pada perusahaan berkategori high profile yang listing di Bursa Efek Indonesia). Nominal: Barometer Riset Akuntansi dan Manajemen, 1(2), 22-34. https://doi.org/10.21831/nominal.v1i2.996 Otoritas Jasa Keuangan. (2016). POJK Nomor 76/POJK.07/2016 tentang Peningkatan Literasi dan Inklusi Keuangan di Sektor Jasa Keuangan Bagi Konsumen dan/atau masyarakat. Rahmawati. (2020). Financial inclusion disclosure in Islamic microfinance: The case of baitul mal wa tamwil. In Enhancing Financial Inclusion through Islamic Finance, Volume 2 (pp. 137-160). Palgrave Macmillan. Ramzan, M., Amin, M., & Abbas, M. (2021). How does corporate social responsibility affect financial performance, financial stability, and financial inclusion in the banking sector? Evidence from Pakistan. Research in International Business and Finance, 55(August 2020). https://doi.org/10.1016/j.ribaf.2020.101314 Scaltrito, D. (2016). Voluntary disclosure in Italy: Firm-specific determinants an empirical analysis of Italian listed companies. EuroMed Journal of Business, 11(2), 272–303. https://doi.org/10.1108/EMJB-07-2015-0032 Sembiring, E. R. (2012). Pengaruh profitabilitas, leverage, struktur kepemilikan dan status perusahaan terhadap pengungkapan laporan keuangan pada perusahaan manufaktur di Indonesia. Diponegoro Journal of Accounting, 1(1), 238–247. Ullah, M.H. and Rahman, M.A. (2015), Corporate social responsibility reporting practices in banking companies in Bangladesh: Impact of regulatory change. Journal of Financial Reporting and Accounting, 13(2), 200-225. https://doi.org/10.1108/JFRA-05-2013-0038 Vo, D.H., Tran, N.P., Hoang, H.T.-T. and Van, L.T.-H. (2022), Do corporate social responsibility and bank performance matter for financial inclusion in Vietnam?, Journal of Asia Business Studies, 16(4), 639-651. https://doi.org/10.1108/JABS-11-2020-0462